SMEs capabilities & performance: The moderating role of environmental turbulence - Ali, Sajjad (2023)
Small medium enterprises (SMEs) act as an engine of economic growth, poverty reduction, and employment creation through new business ventures in any economy. The main objective of this study was to examine the relationship among entrepreneurial orientation, learning orientation, financial literacy, access to finance, entrepreneurial business networks, and SME performance in Pakistan. Furthermore, environmental turbulence was used as a moderating variable between the independent and dependent variables. To fulfill the objective of this study, data were collected from selected Textile SMEs operating in Pakistan. This study employed the simple random sampling technique. The unit of analysis in this was the firms, which were SMEs in Pakistan and the owner/manager of the SMEs were the participants. Five hundred (500) questionnaires were distributed to SMEs owner/manager, but only 379 were deemed usable and completed. The high response rate of 75 percent was achieved due to the survey instrument being personally distributed by the researchers. SPSS 25 software was used to synchronize the data and Smart PLS 2.0 was used to analyze the data. The findings revealed that firm capabilities (LO, FL, AF, and EBN) have a positive and significant effect on SMEs' performance except for EO. Moreover, environmental turbulence (ET) moderates the relationship between EO, LO, AF, EBN, and SMEs performance except for FL. This study concluded that firm capabilities (EO, LO, FL, AF, and EBN) are significantly important for small and medium-sized enterprises and contribute to their overall performance. This study contributes to the extant literature on how ET moderates firm capabilities and SME performance relationships. The research also contributes to RBV and Contingency theories and provides important guidance for managers, researchers, and policymakers in developing strategies. In this study, performance was measured subjectively, while future research could use objective measures of performance.